Polyunsaturated Fatty Acid-Derived Lipid Mediators and T Cell Function - Nicolaou, Anna; Mauro, Claudio; Urquhart, Paula; Marelli-Berg, Federica (Frontiers in Immunology, 2014)
Fatty acids are involved in T cell biology both as nutrients important for energy production as well as signalling molecules. In particular, polyunsaturated fatty acids are known to exhibit a range of immunomodulatory properties that progress through T cell mediated events, although the molecular mechanisms of these actions have not yet been fully elucidated. Some of these immune activities are linked to polyunsaturated fatty acid-induced alteration of the composition of cellular membranes and the consequent changes in signalling pathways linked to membrane raft associated proteins. However, significant aspects of the polyunsaturated fatty acid bioactivities are mediated through their transformation to specific lipid mediators, products of cyclooxygenase, lipoxygenase or cytochrome P450 enzymatic reactions. Resulting bioactive metabolites including prostaglandins, leukotrienes and endocannabinoids are produced by and/or act upon T leukocytes through cell surface receptors and have been shown to alter T cell activation and differentiation, proliferation, cytokine production, motility and homing events. Detailed appreciation of the mode of action of these lipids presents opportunities for the design and development of therapeutic strategies aimed at regulating T cell function.